Man And War: A Study in the Photographs Rahim Hassan- Najman Yassin/ (3GdEfSGf h GdMQH(B- (3bGOSjI UOGe aj CYeGd GdafGf QMje MSf(B- (3fLeGf jGSjfs - Hassan, Rahim; Yassin, Najman; (3QMje MSfs; (3fLeGf jGSjfs ((3HZOGO; s (3efThQGJ GdOGQ GdhWfjI ddJhRjY hGdEYdGf;s, 1986)
(3defGSHI eYQV GdTQb GdcHjQ (B((3GdOhdj GdNGeS ddcJGH(B)s
English; Arabic
Keywords: TR624-835 Technology- Applied Photography; War. Conflict